Polish Rod Displacement Simulation on Sucker Rod Pump Using the Piecewise-Linear Basis Method - I Gde Made Bagus Nurseta Wijaya; Annisa Aditsania; Putu Harry Gunawan (Indonesia Journal on Computing (Indo-JC), 2020)
Sucker Rod Pump (SRP) is a heavy equipment used to pump oil(ﬂuid) from the ground. The purpose of this study is to determine the numerical solution of displacement problems on the polish rod in the sucker rod pump. From previous studies displacement can be simulated and calculated numerical solutions using the Finite Difference method. But in this study the method that will be used is the Piecewise-Linear Base method to simulate displacement on the polish rod and compared to the analytic simulation of the problem. From the simulation results both methods obtained an error rate 2.00911 x 10−17 at ∆x = 0.2, 3.30195 x 10−17 at ∆x = 0.05 and 1.45114 x 10−16 at ∆x = 0.02.